Stabilization method of the single-phase inverters at smart grid application - Wong, Jia Sheng (2019)
Power electronics such as inverter are found in most of the electronic systems. In most commercial and healthcare sectors, where power failure is not an option, it is essential to study the various methods in achieving a stable output voltage. This project aims to fulfil the stability methods of the single-phase inverter where 3 methods such as PI control, PR control and backstepping control are introduced and evaluated. PI and PR control theories are based on Nyquist criteria whereas backstepping control theory is based on Lyapunov criteria. The control methods are designed and implemented in the MATLAB Simulink to analyse their performance. These control methods are capable of stabilizing the single-phase inverter. Specifically, this project focuses on identifying the most effective control method to maintain 230AC voltage by comparing the performance of the 3 control methods under the steady state as well as the transient state. The evaluation of the parameters changes during the transient state were presented. Subsequently, a real-time simulation is also conducted using the OPAL-RT and oscilloscope to observe and verify the output waveform. Lastly, the conclusion and future work recommendations will be shown at the end of the report.